Pengaruh Model Pembelajaran Berbasis Proyek (Project-Based Learning) terhadap Hasil Belajar Kognitif Siswa pada Konsep Keanekaragaman Hayati - Amalia, Nurul; Haerani, Dini (Biocaster : Jurnal Kajian Biologi, 2025)
This research is motivated by the condition of the implementation of learning which mostly still uses lecture-based or conventional learning models, where the learning process carried out is more centered on the educator himself, while students only receive the learning materials given, this affects the cognitive learning outcomes of students. Therefore, educators are required to use a variety of learning models in order to optimize the learning process. The purpose of this study was to determine the effect of the Project-Based Learning Model on the cognitive learning outcomes of students at SMAN 10 Samarinda. This research is a quantitative study with the Quasi Experiment method. The number of samples in this study was 48 respondents consisting of 24 respondents for class X1 and 24 respondents from class X2. The sampling technique in this study used the Purposive Sampling technique. This study uses primary data whose data collection is by distributing test sheets. The results of the study show that the significant value obtained is 0.000 which is far below the significance level (0.05) which indicates that H0 can be rejected, because there is strong evidence that the Project-Based Learning Model has a significant effect on students' cognitive learning outcomes.